2019
DOI: 10.1111/ctr.13745
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy for living donor left nephrectomy: Comparison of three‐dimensional and two‐dimensional vision

Abstract: The main objective of this preliminary study was to evaluate the feasibility and safety of 3‐D laparoscopic living donor left nephrectomy (LDLN). The secondary objective was to compare intraoperative and postoperative outcomes between 3‐D and 2‐D laparoscopic LDLN. All patients who underwent a laparoscopic LDLN from January 2015 to April 2018 in a university center were included. All surgeries were performed by three experienced surgeons. Seventy three patients were included the following: 16 underwent a 3‐D l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This time was similar to the results of Prudhomme et al, who suggested that 3D laparoscopic kidney extraction was significantly superior to 2D laparoscopic system in terms of total operation time (80.9 ± 10.2 vs. 114. 1 ± 32.3 min in 3D and 2D, p = 0.0002) and warm ischemia time (1.7 ± 0.6 vs. 2.3 ± 0.9 min in 3D and 2D, p = 0.02), these findings might be attributed to the improved speed of the 3D laparoscopic system in terms of vessel separation and ligation [ 21 ]. The tumor resection and the transplanted kidney repair were all performed after immersion in cryogenic perfusion fluid.…”
Section: Discussionmentioning
confidence: 99%
“…This time was similar to the results of Prudhomme et al, who suggested that 3D laparoscopic kidney extraction was significantly superior to 2D laparoscopic system in terms of total operation time (80.9 ± 10.2 vs. 114. 1 ± 32.3 min in 3D and 2D, p = 0.0002) and warm ischemia time (1.7 ± 0.6 vs. 2.3 ± 0.9 min in 3D and 2D, p = 0.02), these findings might be attributed to the improved speed of the 3D laparoscopic system in terms of vessel separation and ligation [ 21 ]. The tumor resection and the transplanted kidney repair were all performed after immersion in cryogenic perfusion fluid.…”
Section: Discussionmentioning
confidence: 99%
“…In the available literature, we found only one study that compared 3D and 2D laparoscopic donor nephrectomy [ 28 ]. Therefore, we believe that the number of such articles is not enough to show statistically meaningful differences.…”
Section: Discussionmentioning
confidence: 99%